A generalizable formalism for computing uncertainties in UTC. (15th October 2020) - Matsakis, Demetrios
Abstract: Algorithms to compute the statistical and systematic uncertainties in the difference between Coordinated Universal Time (UTC) and individual laboratory UTC realizations were published in several different, but equivalent, forms the early twenty-first century, at a time when the UTC algorithm was based on a minimal network. In this paper we extend the theory to compute the uncertainties in a manner entirely consistent with the earlier work, but which enables application to UTC computations employing redundant links, and correlated calibrations.